Omegan naphthalene plant - Lirag, Rufino C. Jr (College of Engineering, 1962)
The total investment according to cost estimates prior to full scale production is 506,527.21. All other expenses including operational costs, financial obligations amounts to 309,526.00 giving a net capital investment of 816,053.21. To operate 24 hours a day and 300 days in a year gives an annual production capacity of 450 tons from which sales amounts to 340,000 based on the unit cost of product which is P 3.00 per kilo.